The mRNA encoding TAFI is alternatively spliced in different cell types and produces intracellular forms of the protein lacking TAFIa activity - Lin, Joellen H. H.; Novakovic, Dragana; Rizzo, Christina M.; Zagorac, Branislava; Garand, Mathieu; Filipieva, Anastassia; Koschinsky, Marlys L.; Boffa, Michael B. (Thrombosis and Haemostasis, 2013)
TAFI (thrombin-activatable fibrinolysis inhibitor) is a pro-carboxypeptidase, encoded by the CPB2 gene in humans that links the coagulation cascade to fibrinolysis and inflammation. The liver is the main source for plasma TAFI, and TAFI expression has been documented in platelets and monocyte-derived macrophages. A recent study reported an alternatively spliced CPB2 mRNA variant lacking exon 7 (Δ7) in HepG2 cells and liver. Another study identified a CPB2 mRNA variant lacking exon 7 and a 52 bp deletion in exon 11 (Δ7+11) in human hippocampus. We have examined alternative splicing of CPB2 mRNA in various cell types by RT-PCR and have assessed the functional properties of TAFI variants encoded by these transcripts by recombinant expression in mammalian cells. We identified the Δ7 exon skipping event in liver, Dami megakaryoblasts, THP-1-derived macrophages, peripheral blood mononuclear cells, platelets, testis, cerebellum, and SH-SY5Y neuroblastoma cells. The Δ11 alternative splicing event was notably absent in liver cells. We also detected a novel exon Δ7+8 skipping event in liver and megakaryocytes. Of note, we detected non-alternatively spliced CPB2 transcripts in brain tissues, suggesting the expression of full-length TAFI in brain. Experiments using cultured mammalian cells transfected with wild-type CPB2-, Δ7-, Δ7+11 -, and_Δ11 -cDNA revealed that alternatively spliced TAFI is stored inside the cells, cannot be activated by thrombin-thrombomodulin, and does not have TAFIa activity. The alternative splicing events clearly do not give rise to a secreted protein with basic carboxy-peptidase activity, but the intracellular forms may possess novel functions related to intracellular proteolysis.
Keywords: Thrombin-activatable fibrinolysis inhibitor (TAFI); alternative splicing; liver; brain; monocytes/macrophages; megakaryocytes